Unconventional Computation and Natural Computation 20th International Conference, UCNC 2023, Jacksonville, FL, USA, March 13-17, 2023, Proceedings - Genova, Daniela; Kari, Jarkko (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the proceedings of the 20th International Conference on Unconventional Computation and Natural Computation, UCNC 2023, held in Jacksonville, FL, USA, in March 13-17, 2023. The UCNC conference series covers fundamental research on computation beyond the standard Turing model, including computational models and methods inspired by nature, and the computational properties of natural processes.
An investigation to test spectral segments as bacterial biomarkers -- Robot Relocation is Hard in only two Directions even without Obstacles -- Robert Schweller and Tim Wylie Generically Computable Abelian Groups -- Extraction Rates of Random Continuous Functionals -- Computing with nanowire exchange-coupled spin torque oscillator arrays -- Stepney Tight bounds on the directed tile complexity of a just-barely 3D $2 \times N$ rectangle at temperature 1 -- Robustness of Magnetic Ring Arrays Reservoir Computing with Linear Field Calibration -- The Topological Entropy of Reversible Cellular Automata and Related Problems -- Toni Hotanen Fault Pruning: Robust Training of Neural Networks with Memristive Weights -- Spatial correlations in the qubit properties of D-Wave 2000Q measured and simulated qubit networks -- Simulation of Multiple Stages in Single Bin Active Tile Self-Assembly -- Single-Shuffle Card-based Protocol with Eight Cards per Gate -- Modelling and Evaluating Restricted ESNs.
Keywords: Computer science; Computer Science Logic and Foundations of Programming